Evaluación de tiras reactivas de urianálisis de uso humano en medicina veterinaria en la clínica veterinaria de la Universidad Estatal de Bolívar - Yánez Berrones, David Stalin (2023)
University Clinic was conducted, the following research project, with patients who attended consultation taking their physiological constants, The respective anamnesis to be taken in the urinalysis tests are the physical and chemical analysis, in which we will evaluate the appearance, coloration of the urine, in the chemical analysis we will observe the various parameters found in the test strips such as ketones, glucose, leukocytes, etc.. With which it will be determined, if the use of the reactive strips of human use could be useful in the daily clinic to give presumptive diagnoses together with more laboratory tests to reach a correct diagnosis, this would help abysmally for the cheapening of costs for the clinic or veterinary hospital, with the good use of the laboratory materials and the recommended by the manufacturer we will have more innocuousness of the samples to be able to reach the objective of an accurate diagnosis for the affection of each patient. In the analytes under study in the glucose we obtain that the test strip for human use has no reaction to the patient's urine with 100% negativity, on the other hand in the test strip for veterinary use we have a minimal reaction on the part of glucose with 3% to give positive to a glucosuria. Bilirubin has variation in the human use test strip with percentages within 4% and 1% with alterations in its parameters and normal parameters of 95%. Followed by the veterinary use test strip that only has 1% in the parameter that is out of the normal and with a result in negativity of 99%. The data collected in nitrites did not have any type of alteration of the parameters in the variable nitrites giving both test strips a value of 100% of negativity in them. This gives us indications of small variations based on the data and have alterations at the time of giving results. It is always advisable to use more than one diagnostic test to complement the urinalysis test, especially pH and density.